Perbedaan Efektifitas Madu dan Air Gula Terhadap Nyeri Injeksi Imunisasi Campak Bayi Usia 9-15 Bulan Puskesmas Lubuk Buaya Tahun 2019 - Dewi Susanti; Alsri Windra Doni; Rizqi Twin Desfialni Putri (Jurnal Sehat Mandiri, 2019)
Coverage of measles immunization in Padang city is 88.8%, while the target of achieving national measles immunization is 95%. The reason a child is not immunized is 27.5% because it is delayed at another time. Pain management of nonpharmacological immunization with honey and sugar water can increase comfort so as to avoid delaying at another time. The purpose of this study was to determine the differences in the effectiveness of honey and sugar water against the pain of measles immunization injection in infants aged 9-15 months. This type of research is a Quasi experiment with post test only design. sampling with a sample size of 32 people. Pain score data obtained from observation sheets and analyzed univariately and bivariately using an independent t test with computerization. The results of the study mean the pain score in the honey group was 1.19 while the mean pain score in the sugar water group was 1.88. After an independent t test was obtained p value = 0.038 (α <0.05) means that there is a difference in the effectiveness of honey and sugar water against the pain of measles immunization injection. The results of the study concluded that honey was more effective on measles immunization injection pain scores. The suggestion of this study was to improve the comfort of children by minimizing the pain of immunization injection using honey and sugar water.